1991
DOI: 10.1159/000463195
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Rabbit C3: Studies of the Generation of Cleavage Products in vitro and of Their Metabolism in vivo

Abstract: The cleavage of purified, functionally active rabbit C3 by cobra venom factor and trypsin was analysed by reducing and non-reducing sodium dodecyl sulphate electrophoresis and autoradiography. The specific aim of the study was to compare these reactions to those that occur with human C3. Analysis showed that the pattern of breakdown was very similar to that for the human protein: while the ß-chain remained intact, there was step-wise degradation of the α-chain to form C3a, C3b, iC3b and C3c, all of which could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Thus C3, the third component of human complement, has a T1/2 in the rabbit of approximately 37 h, but 70 h in man (21). In comparison, rabbit C3 has a T1/2 of 29 h when reinjected into rabbits (21). The comparability of our data on the behaviour of the adiponectin-related molecule C1q in the rabbit to published turnover data on C1q in man (22,23) supports our conclusions on the metabolic behaviour of adiponectin.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Thus C3, the third component of human complement, has a T1/2 in the rabbit of approximately 37 h, but 70 h in man (21). In comparison, rabbit C3 has a T1/2 of 29 h when reinjected into rabbits (21). The comparability of our data on the behaviour of the adiponectin-related molecule C1q in the rabbit to published turnover data on C1q in man (22,23) supports our conclusions on the metabolic behaviour of adiponectin.…”
Section: Discussionsupporting
confidence: 87%
“…As well, adiponectin was relatively long-lived in comparison with other hormones, with an average half-life in the rabbit of approximately 14 h. This figure may be underestimated, as human proteins typically exhibit more rapid metabolism in the rabbit than in man. Thus C3, the third component of human complement, has a T1/2 in the rabbit of approximately 37 h, but 70 h in man (21). In comparison, rabbit C3 has a T1/2 of 29 h when reinjected into rabbits (21).…”
Section: Discussionmentioning
confidence: 98%
“…Whereas act‐C3 is detectable for only a limited period after deposition,16 C4d, the stable split product of C4, can be detected for 4 to 8 days after deposition,17 giving a better indication of complement activation over time. Moreover, because C4 figures in the classical and lectin pathway but not in the alternative complement pathway, C4d detection gives information on the pathways involved in C3 activation.…”
Section: Resultsmentioning
confidence: 99%
“…Metabolic studies in vivo have shown that C3-derived breakdown products equilibrate rapidly between the intravascular and extravascular compartments. 25 Proposed links between C3 and lipid metabolism depend on mechanisms that include the production of ASP and deposition of C3 in atherosclerotic lesions. The ASP hypothesis postulates that chylomicrons act as a catalyst to produce ASP in the capillary via the alternative pathway of complement.…”
Section: Discussionmentioning
confidence: 99%